Enhancing endometrial receptivity in FET cycles: exploring the influence of endometrial and subendometrial blood flow along with endometrial volume - Hazari, Vajihe; Sarvi, Fatemeh; Alyasin, Ashraf; Agha-Hosseini, Marzieh; Hosseinimousa, Sedigheh (Frontiers in Medicine, 2024)
Fetal health and a receptive and healthy endometrium are two essential factors in achieving successful implantation. If the endometrium is unreceptive, postponing the transfer cycle to a suitable time can enhance the chances of pregnancy. This study aims to assess the impact of endometrial and sub-endometrial blood flows measured by Doppler ultrasound, as well as endometrial volume, on endometrial receptivity in frozen embryo transfer (FET) cycles.112 patients with a mean age of 33.93±4.93 years underwent in vitro fertilization (IVF). Serum β-hCG level was used to confirm pregnancy, and among the participants, 50 (44.6%) achieved pregnancy after IVF. The study results revealed a significant difference in endometrial blood flow between the pregnant and non-pregnant groups, with a higher pregnancy rate observed in participants exhibiting multi-focal and spare endometrial blood flows (P<0.05). Furthermore, there was a notable association between endometrial blood flow and pregnancy outcome, as indicated by higher ongoing pregnancy rates in those with multi-focal and spare endometrial blood flows (P<0.05). However, no significant differences were observed in endometrial variables such as volume, length, width, thickness, and pattern between the pregnant and nonpregnant groups. Additionally, contextual parameters showed no significant relationship with pregnancy outcome (P>0.05). The study also found that endometrial measurement indices did not have a significant impact on pregnancy outcomes, with no significant differences observed between the groups (P>0.05).In conclusion, endometrial blood flow is crucial for a successful pregnancy after IVF, while the predictive value of the endometrial volume is limited for pregnancy outcomes.